2015
DOI: 10.15406/jcpcr.2015.02.00025
|View full text |Cite
|
Sign up to set email alerts
|

Thymoma: A Retrospective Review of 55 Cases of Thymoma Treated At a Regional Cancer Center

Abstract: vena vava; KMIO, Kidwai memorial institute of oncology Mini review Resulti. Demographic characteristics of the 50 patients included the following (Table 1).ii. The majority of patients in our series were female 61% (n = 31)iii. Overall average age of patients was 51.0 years. iv. 15(30%) patients were associated with myasthenia gravis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
(20 reference statements)
1
2
0
Order By: Relevance
“…22 Together, B2 and B3 subtypes constituted more than 80% of our patient population. In our study, Masaoka-Koga stages IIIB, IVA, and IVB constituted 60% of the patient population, with IIIB being the commonest stage, similar to previous reported studies from India 29 30 but contrary to Rathod et al where stages I to II were the commonest. 21 The sites of metastases in our cohort included pleura and lung in two patients and lung in one patient.…”
Section: Discussionsupporting
confidence: 91%
“…22 Together, B2 and B3 subtypes constituted more than 80% of our patient population. In our study, Masaoka-Koga stages IIIB, IVA, and IVB constituted 60% of the patient population, with IIIB being the commonest stage, similar to previous reported studies from India 29 30 but contrary to Rathod et al where stages I to II were the commonest. 21 The sites of metastases in our cohort included pleura and lung in two patients and lung in one patient.…”
Section: Discussionsupporting
confidence: 91%
“…Global data have reported no sex predilection for TETs; however, the Indian studies had shown male predominance similar to the observation in the present series101415171823. Only two studies from India demonstrated a female-predominant population1316.…”
Section: Discussionsupporting
confidence: 83%
“…Its incidence in the Indian population has not been defined and in the power analysis carried out by Marchevsky et al 11, only 20 cases of thymomas were included from India. Among the Indian studies with more than 10 cases121314151617181920, Julka et al 18 had the largest sample with 71 cases (all thymomas) from the same centre; however, histomorphological spectrum was not described in this study. Except for studies by Vaideeswar et al 19 and Sundaram et al 20, none of the studies assessed the histomorphology of TET, especially thymic carcinomas.…”
Section: Discussionmentioning
confidence: 68%
“…Indian studies have shown male preponderance same like in our study [5,8] . Few studies on thymoma have shown female preponderance in indian patients [9] . Thymomas are frequent in the age group of 40-60 yrs, but a wide range has been reported from <10 yrs to >80 yrs [10] .…”
Section: Discussionmentioning
confidence: 99%